Nieważność jako skutek wyroku Trybunału Konstytucyjnego w sferze stanowienia prawa - Radziewicz, Piotr (Kwartalnik Prawa Publicznego, 2012)
The article provides a critical analysis of the “invalidity” of legal provisions, as a result of the judgment of the Constitutional Tribunal, and the so called “restoration” of binding force of the provisions by reason of the repeal of the provision that has previously amended it (or has given it a completely or partly new wording), or that has derogated it, means that the legal lacuna resulting from the declaration of the constitutional court finding the legal provision unconstitutional is filled on the basis of the decision of that court. To explain the mechanism of “invalidity” and “revival” of legal provisions, the author discusses also the following issues: the scope of the Constitutional Tribunal’s competence to amending provisions, effects of the Tribunal’s judgments and potential grounds for “invalidity” and “revival” of legal provisions, the nature of derogation made by the constitutional court, constitutional system of sources of law, tribunal’s impact on the parliamentary legislative process (law-making system) and Polish legal system. The actions of the Constitutional Tribunal – author declares – are evident signs of an excessive activism of the Polish constitutional court and may cause doubts in the light of the tripartite principle of separation of powers.